Ceramic substrate for heat sink and preparation process thereof

By using composite AlN-SiC materials in ceramic substrates and filling metal W to form a fast heat dissipation channel and depositing a TiAlN transition layer, the problem of insufficient heat dissipation ability of ceramic substrates in high-power applications is solved, and the high mechanical strength of ceramic substrates is achieved , good heat dissipation performance and strong binding force.

CN119419181AActive Publication Date: 2025-02-11DONGGUAN PEPPER GRAY TECHNOLOGY CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510020706.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-02-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

There are irreconcilable contradictions in the improvement of mechanical strength, heat dissipation performance and bonding strength with metal layer, resulting in insufficient heat dissipation capability in high-power applications.

Method used

A composite AlN-SiC ceramic substrate is used, and metal is filled inside it to form a fast heat dissipation channel, and then a TiAlN transition layer is deposited to improve the overall performance of the ceramic substrate.

Benefits of technology

The high mechanical strength, good heat dissipation performance and strong binding force of the ceramic substrate are achieved, and the comprehensive performance of the ceramic substrate is balanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a ceramic substrate for a heat sink and a preparation process thereof, the ceramic substrate for the heat sink comprises a composite AlN-SiC ceramic base layer and a TiAlN coating deposited on the surface of the composite AlN-SiC ceramic base layer, the composite AlN-SiC ceramic base layer is internally provided with a plurality of blind holes, and the blind holes are filled with metal W; the AlN-SiC material with high mechanical strength is used as the ceramic base layer, the interior of the ceramic base layer is filled with the metal W to form the rapid heat dissipation channel, and then the TiAlN transition layer is deposited, so that the binding force between the obtained ceramic substrate for the heat sink and the metal layer is strong, and the mechanical strength and the heat dissipation performance of the ceramic substrate are not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a ceramic substrate for a heat sink and a preparation process thereof. Background Art

[0002] As the power density of electronic devices continues to increase, the performance requirements for ceramic substrates used in heat sinks are also getting higher and higher. An ideal ceramic substrate should have excellent mechanical strength, good heat dissipation performance, and high bonding strength with the metal layer. However, existing technologies face significant contradictions and challenges in achieving these properties.

[0003] Specifically, in order to apply the ceramic substrate to the field of heat sinks, it needs to have a high thermal conductivity to effectively conduct heat, and needs to have a high mechanical strength for subsequent metal graphics and other processing. However, in the related technology, in order to maintain the mechanical strength of the material, it is usually necessary to sacrifice a certain thermal conductivity, which limits the heat dissipation capacity of the ceramic substrate in high-power applications; in addition, the improvement of the bonding strength between the ceramic substrate and the metal layer is often accompanied by an increase in the number of pore defects inside the ceramic, which will lead to a decrease in the heat dissipation performance and mechanical strength of the ceramic substrate. In summary, the existing technology has irreconcilable contradictions in improving the mechanical strength, heat dissipation performance and bonding strength of the ceramic substrate with the metal layer.

[0004] Therefore, a new technical solution is urgently needed to balance these properties to meet the stringent requirements of high-power electronic devices for ceramic substrates used as heat sinks. Summary of the invention

[0005] In view of the defects in the prior art, the present invention proposes a ceramic substrate for a heat sink and a preparation process thereof to solve the problem of how to improve the comprehensive performance of the ceramic substrate for a heat sink.

[0006] In order to solve the above technical problems, this application provides the following technical solutions.

[0007] In a first aspect, the present application provides a ceramic substrate for a heat sink, comprising a composite AlN-SiC ceramic base layer, a TiAlN coating deposited on the surface of the composite AlN-SiC ceramic base layer, a plurality of blind holes being arranged inside the composite AlN-SiC ceramic base layer, and metal W being filled in the blind holes.

[0008] Preferably, the thermal conductivity of metal W is greater than the thermal conductivity of AlN—SiC.

[0009] Preferably, the thickness of the TiAlN coating is 100-300 nm.

[0010] In a second aspect, the present application provides a method for preparing a ceramic substrate for a heat sink, comprising the following steps: S1. Using AlN-SiC, a sintering aid, a binder, and an organic solvent as raw materials, a composite AlN-SiC ceramic substrate is obtained by tape casting; S2. Using a laser drilling process, punching holes on the composite AlN-SiC ceramic substrate to obtain a composite AlN-SiC ceramic substrate having a blind hole; S3. Filling the blind hole with metal W slurry to obtain a composite substrate; S4. In-situ depositing a TiAlN coating on the composite substrate to obtain a ceramic substrate for a heat sink.

[0011] Preferably, in step S1, the sintering aid includes one or more of yttrium oxide and yttrium fluoride; the binder includes one or more of polyvinyl alcohol and polyvinyl pyrrolidone; and the organic solvent includes one or more of ethanol, n-butanol, and triethyl phosphate.

[0012] Preferably, in step S1, the sintering temperature of the tape casting method is 1600-1700°C.

[0013] Preferably, between step S2 and step S3, the method further includes the step of immersing the composite AlN-SiC ceramic substrate provided with the blind holes in a phosphoric acid solution.

[0014] Preferably, in step S3, after filling the metal W slurry, a polishing step is also included.

[0015] Preferably, in step S4, the step of in-situ depositing the TiAlN coating is: using trimethylaluminum, titanium tetrachloride and ammonia as precursors, utilizing a thermal atomic layer deposition process to prepare the TiAlN coating on the composite substrate.

[0016] In a third aspect, the present application provides an application of a heat sink ceramic substrate in a heat sink assembly.

[0017] Compared with the prior art, the present invention achieves the following technical effects: in the present application, by using AlN-SiC material with high mechanical strength as the ceramic base layer, and filling metal W inside it to form a rapid heat dissipation channel, and then depositing a TiAlN transition layer, the obtained ceramic substrate for the heat sink can have a strong bonding force with the metal layer, and the ceramic substrate has high mechanical strength and good heat dissipation performance. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0019] The present application provides a ceramic substrate for a heat sink, comprising a composite AlN-SiC ceramic base layer and a TiAlN coating deposited on the surface of the composite AlN-SiC ceramic base layer. The composite AlN-SiC ceramic base layer is provided with a plurality of blind holes filled with metal W.

[0020] In the scheme of the present application, AlN-SiC material is used as the ceramic base layer, which can not only make up for the defects of easy hydrolysis of AlN and low density of SiC, but also ensure that the ceramic base layer has the advantages of AlN and SiC, such as high thermal conductivity, high insulation, and high hardness. At the same time, since AlN and SiC have similar density and thermal expansion coefficient, the ceramic base layer has high density and good mechanical properties, which provides a mechanical basis for subsequent drilling and filling, and overcomes the defects of reduced mechanical strength and fragmentation of the ceramic substrate caused by drilling and filling W metal. In the present application, metal W is filled in the composite AlN-SiC ceramic base layer. On the one hand, metal W has higher thermal conductivity than the AlN-SiC ceramic base layer, which can form a rapid heat dissipation channel and improve the heat dissipation performance of the ceramic substrate. On the other hand, After oxidation, the TiAlN layer will form an oxide layer with lower thermal conductivity. By using W in close contact with the TiAlN layer, W can inhibit the phase transformation of TiO2, thereby improving the oxidation resistance of the TiAlN layer and avoiding the problem of reduced thermal conductivity of the TiAlN layer due to oxidation. In the present application, a transition layer TiAlN layer is deposited on a composite AlN-SiC ceramic base layer filled with metal W. Due to the large difference in thermal expansion coefficient between the ceramic substrate and the subsequent metal coating (such as a copper layer), the TiAlN layer can reduce the interface stress between the ceramic substrate and the subsequent metal coating (such as a copper layer), improve the bonding strength between the ceramic substrate and the subsequent metal coating (such as a copper layer), and finally achieve a balance between the mechanical properties, thermal conductivity and bonding ability of the ceramic substrate with the metal layer.

[0021] In some embodiments, the thermal conductivity of metal W is greater than the thermal conductivity of AlN—SiC.

[0022] In the application, the thermal conductivity of metal W is generally 170-180W / (m·K), and the thermal conductivity of AlN-SiC in the present application is lower than that of metal W, so that the formation of a heat dissipation channel can be realized. If the thermal conductivity of AlN-SiC is equal to or lower than that of the metallized material W, the heat flux density distribution is relatively uniform, and it is not easy to form a heat dissipation channel, and the effect of improving the heat dissipation performance is not obvious.

[0023] In the present application, the preparation method of AlN-SiC material is as follows: silicon powder, carbon black and aluminum nitride are put into a ball mill for ball milling, the balls are separated by a sieve to obtain a uniformly mixed powder, and then the mixed powder is put into a graphite crucible for vacuum sintering to obtain AlN-SiC material.

[0024] In some embodiments, the blind holes are distributed in an array, the diameter of the blind holes is 0.15-0.2 mm, the spacing between adjacent blind holes is 0.4-0.8 mm, the size of the ceramic substrate for the heat sink is (8-10) mm*(8-10) mm, the thickness of the ceramic substrate for the heat sink is 0.8-1.0 mm, and the depth of the blind holes is 0.5-0.7 mm.

[0025] In this embodiment, the blind holes are arranged in an array distribution manner as defined in the present application, so as to achieve a balance between heat dissipation and mechanical performance. If the pores are too dense, the mechanical performance is poor, and if the pores are too loose, the heat dissipation performance is poor.

[0026] The thickness of the TiAlN coating is 100-300 nm.

[0027] In this embodiment, the TiAlN coating has excellent properties such as high hardness, high oxidation temperature, good thermal hardness, strong adhesion, and small friction coefficient. The thickness of the TiAlN coating is within a limited range, which can achieve a balance between heat dissipation and mechanical properties. If the TiAlN coating is too thick, the heat dissipation performance of the ceramic substrate will be reduced. If the TiAlN coating is too thin, it will affect the bonding strength between the ceramic substrate and the subsequent metal coating.

[0028] The present application provides a method for preparing a ceramic substrate for a heat sink, comprising the following steps: S1. Using AlN-SiC, a sintering aid, a binder, and an organic solvent as raw materials, a composite AlN-SiC ceramic substrate is obtained by tape casting; S2. Using a laser drilling process, punching holes on the composite AlN-SiC ceramic substrate to obtain a composite AlN-SiC ceramic substrate having a blind hole; S3. Filling the blind hole with metal W slurry to obtain a composite substrate; S4. In-situ depositing a TiAlN coating on the composite substrate to obtain a ceramic substrate for a heat sink.

[0029] In the embodiments of the present application, a ceramic substrate is obtained by tape casting-laser drilling-hole filling-in-situ deposition of a transition layer. The process flow is short, and the blind hole distribution, filling metal type, and transition layer thickness are all controllable, which is conducive to obtaining a ceramic substrate for a heat sink with good comprehensive performance.

[0030] In some embodiments, in step S1, the sintering aid includes one or more of yttrium oxide and yttrium fluoride; the binder includes one or more of polyvinyl alcohol and polyvinyl pyrrolidone; and the organic solvent includes one or more of ethanol, n-butanol, and triethyl phosphate.

[0031] In this embodiment, the sintering aid is helpful to reduce the sintering temperature of the tape casting method, the binder is helpful to improve the strength of the composite AlN-SiC ceramic base layer, and the organic solvent does not contain aldehydes, ketones, and aromatic hydrocarbons and has good compatibility with the sintering aid and the binder.

[0032] In some embodiments, in step S1, the sintering temperature of the tape casting method is 1600-1700°C.

[0033] In this embodiment, the sintering process can be performed at 1600-1700° C. The low sintering temperature is beneficial to the stability of the composite AlN-SiC ceramic substrate, thereby improving the mechanical strength of the AlN-SiC ceramic substrate.

[0034] In some embodiments, between step S2 and step S3, there is also a step of immersing the composite AlN-SiC ceramic substrate having the blind holes in a phosphoric acid solution.

[0035] In this embodiment, since the present application utilizes laser drilling, laser processing of the ceramic substrate will result in slag on the micropore surface and roughness inside the pores, which will affect the filling of metal W. At the same time, the action of the laser and AlN will easily cause Al to precipitate, turning AlN, which is originally an insulator, into a semiconductor, affecting the insulation performance of the substrate. Therefore, in this embodiment, the removal of Al precipitated by laser processing of the AlN substrate can be achieved through phosphoric acid immersion, thereby ensuring the insulation of the substrate and reducing the slag on the micropore surface and roughness inside the pores of the ceramic substrate.

[0036] In some embodiments, in step S3, after filling the metal W slurry, a polishing step is also included.

[0037] In this embodiment, the metal W slurry is first filled, then sintered and polished, and the cycle is repeated 3-5 times. The metal slurry at the through hole opening is completely filled and flattened by repeated filling, sintering and polishing, which is more conducive to the deposition of the TiAlN coating.

[0038] In some embodiments, in step S4, the step of in-situ depositing the TiAlN coating is: using trimethylaluminum, titanium tetrachloride, and ammonia as precursors, and utilizing a thermal atomic layer deposition process to prepare the TiAlN coating on the composite substrate.

[0039] In this embodiment, the specific steps of in-situ deposition of TiAlN coating are: heating the composite substrate to 100°C, and adsorbing titanium tetrachloride onto the surface of the composite substrate under a pressure of 50Pa, then adding trimethylaluminum, fumigating for 60s, then flushing away excess TMA with inert gas, and then dripping ammonia water to react to form a TiAlN layer. The above steps constitute an in-situ deposition cycle, and repeating these steps can gradually increase the thickness of the film.

[0040] The present application provides an application of a ceramic substrate for a heat sink in a heat sink assembly.

[0041] Source of raw materials: Metal W powder: CAS number is 7440-33-7, thermal conductivity is 174 W / (m·K).

[0042] AlN-SiC: 100g silicon powder, 120g carbon black and 80g aluminum nitride were put into a ball mill and milled. The balls were separated by sieve to obtain a uniformly mixed powder. The mixed powder was then put into a graphite crucible and vacuum sintered at 1800℃ for 3h to obtain AlN-SiC material. The thermal conductivity of the AlN-SiC material was measured to be 52.7W / (m·K).

[0043] Example 1 A ceramic substrate for a heat sink comprises a composite AlN-SiC ceramic base layer and a TiAlN coating deposited on the surface of the composite AlN-SiC ceramic base layer, wherein a plurality of blind holes are arranged inside the composite AlN-SiC ceramic base layer, and the blind holes are filled with metal W, wherein the blind holes are distributed in an array, the diameter of the blind holes is 0.2 mm, and the spacing between adjacent blind holes is 0.4 mm. The size of the ceramic substrate for the heat sink is 8 mm*8 mm, the thickness of the ceramic substrate for the heat sink is 1.0 mm, the depth of the blind holes is 0.7 mm, and the thickness of the TiAlN coating is 300 nm.

[0044] A method for preparing a ceramic substrate for a heat sink comprises the following steps: S1. 100gAlN-SiC powder, 5g yttrium oxide, 200ml n-butanol were mixed and ball-milled, and then 3g polyvinyl alcohol was added to obtain a slurry. The front blade height of the casting machine was set to 2.0mm, the rear blade height was 1.5mm, and the casting speed was 0.20m / min. The slurry after degassing was poured into the casting machine film belt and dried for 2 hours at a variable temperature to obtain a 0.75mm thick blank. The blank was placed in a graphite hot pressing sintering furnace, and the fluid nitrogen atmosphere was sintered under positive pressure. The N2 pressure was set at 20KPa, the sintering temperature was 1600°C, and the holding time was 5 hours to obtain a composite AlN-SiC ceramic base; S2. Punching holes on the composite AlN-SiC ceramic substrate using a laser punching process to obtain a composite AlN-SiC ceramic substrate with blind holes, wherein the blind holes are distributed in an array, the diameter of the blind holes is 0.2 mm, the spacing between adjacent blind holes is 0.4 mm, the size of the heat sink ceramic substrate is 8 mm*8 mm, the thickness of the heat sink ceramic substrate is 1.0 mm, and the depth of the blind holes is 0.7 mm. Then, the composite AlN-SiC ceramic substrate with blind holes is immersed in 200 ml of phosphoric acid, immersed for 1 hour and taken out; S3. Injecting molten metal W slurry into the blind hole, sintering at 1500°C and polishing, cyclically sintering - polishing steps 3 times to obtain a composite substrate; S4. Heat the composite substrate to 100°C, and adsorb 1g of titanium tetrachloride onto the surface of the composite substrate under a pressure of 50Pa, then add 2g of trimethylaluminum, fumigate for 60s, then flush out excess TMA with inert gas, and then drop 5ml of ammonia water to react to form a TiAlN layer with a thickness of 50nm. Repeat the above steps 6 times, and the thickness of the TiAlN layer is 300nm, thus obtaining a ceramic substrate for heat sink.

[0045] Example 2 A ceramic substrate for a heat sink comprises a composite AlN-SiC ceramic base layer and a TiAlN coating deposited on the surface of the composite AlN-SiC ceramic base layer, wherein a plurality of blind holes are arranged inside the composite AlN-SiC ceramic base layer, and the blind holes are filled with metal W, wherein the blind holes are distributed in an array, the diameter of the blind holes is 0.15 mm, and the spacing between adjacent blind holes is 0.8 mm. The size of the ceramic substrate for the heat sink is 8 mm*8 mm, the thickness of the ceramic substrate for the heat sink is 1.0 mm, the depth of the blind holes is 0.7 mm, and the thickness of the TiAlN coating is 300 nm.

[0046] A method for preparing a ceramic substrate for a heat sink comprises the following steps: S1. 100gAlN-SiC powder, 5g yttrium oxide, 200ml n-butanol were mixed and ball-milled, and then 3g polyvinyl alcohol was added to obtain a slurry. The front blade height of the casting machine was set to 2.0mm, the rear blade height was 1.5mm, and the casting speed was 0.20m / min. The slurry after degassing was poured into the casting machine film belt and dried for 2 hours at a variable temperature to obtain a 0.75mm thick blank. The blank was placed in a graphite hot pressing sintering furnace, and the fluid nitrogen atmosphere was sintered under positive pressure. The N2 pressure was set at 20KPa, the sintering temperature was 1600°C, and the holding time was 5 hours to obtain a composite AlN-SiC ceramic base; S2. Punching holes on the composite AlN-SiC ceramic substrate using a laser punching process to obtain a composite AlN-SiC ceramic substrate with blind holes, wherein the blind holes are distributed in an array, the diameter of the blind holes is 0.2 mm, the spacing between adjacent blind holes is 0.8 mm, the size of the heat sink ceramic substrate is 8 mm*8 mm, the thickness of the heat sink ceramic substrate is 1.0 mm, and the depth of the blind holes is 0.7 mm. Then, the composite AlN-SiC ceramic substrate with blind holes is immersed in 200 ml of phosphoric acid, immersed for 1 hour and taken out; S3. Injecting molten metal W slurry into the blind hole, sintering at 1500°C and polishing, cyclically sintering - polishing steps 3 times to obtain a composite substrate; S4. Heat the composite substrate to 100°C, and adsorb 1g of titanium tetrachloride onto the surface of the composite substrate under a pressure of 50Pa, then add 2g of trimethylaluminum, fumigate for 60s, then flush out excess TMA with inert gas, and then drop 5ml of ammonia water to react to form a TiAlN layer with a thickness of 50nm. Repeat the above steps 6 times, and the thickness of the TiAlN layer is 300nm, thus obtaining a ceramic substrate for heat sink.

[0047] Example 3 A ceramic substrate for a heat sink comprises a composite AlN-SiC ceramic base layer and a TiAlN coating deposited on the surface of the composite AlN-SiC ceramic base layer, wherein a plurality of blind holes are arranged inside the composite AlN-SiC ceramic base layer, and the blind holes are filled with metal W, wherein the blind holes are distributed in an array, the diameter of the blind holes is 0.2 mm, and the spacing between adjacent blind holes is 0.3 mm. The size of the ceramic substrate for the heat sink is 8 mm*8 mm, the thickness of the ceramic substrate for the heat sink is 1.0 mm, the depth of the blind holes is 0.7 mm, and the thickness of the TiAlN coating is 300 nm.

[0048] A method for preparing a ceramic substrate for a heat sink comprises the following steps: S1. 100gAlN-SiC powder, 5g yttrium oxide, 200ml n-butanol were mixed and ball-milled, and then 3g polyvinyl alcohol was added to obtain a slurry. The front blade height of the casting machine was set to 2.0mm, the rear blade height was 1.5mm, and the casting speed was 0.20m / min. The slurry after degassing was poured into the casting machine film belt and dried for 2 hours at a variable temperature to obtain a 0.75mm thick blank. The blank was placed in a graphite hot pressing sintering furnace, and the fluid nitrogen atmosphere was sintered under positive pressure. The N2 pressure was set at 20KPa, the sintering temperature was 1600°C, and the holding time was 5 hours to obtain a composite AlN-SiC ceramic base; S2. Punching holes on the composite AlN-SiC ceramic substrate using a laser punching process to obtain a composite AlN-SiC ceramic substrate with blind holes, wherein the blind holes are distributed in an array, the diameter of the blind holes is 0.3 mm, the spacing between adjacent blind holes is 0.8 mm, the size of the heat sink ceramic substrate is 8 mm*8 mm, the thickness of the heat sink ceramic substrate is 1.0 mm, and the depth of the blind holes is 0.7 mm. Then, the composite AlN-SiC ceramic substrate with blind holes is immersed in 200 ml of phosphoric acid, immersed for 1 hour and taken out; S3. Injecting molten metal W slurry into the blind hole, sintering at 1500°C and polishing, cyclically sintering - polishing steps 3 times to obtain a composite substrate; S4. Heat the composite substrate to 100°C, and adsorb 1g of titanium tetrachloride onto the surface of the composite substrate under a pressure of 50Pa, then add 2g of trimethylaluminum, fumigate for 60s, then flush out excess TMA with inert gas, and then drop 5ml of ammonia water to react to form a TiAlN layer with a thickness of 50nm. Repeat the above steps 6 times, and the thickness of the TiAlN layer is 300nm, thus obtaining a ceramic substrate for heat sink.

[0049] Example 4 A ceramic substrate for a heat sink comprises a composite AlN-SiC ceramic base layer and a TiAlN coating deposited on the surface of the composite AlN-SiC ceramic base layer, wherein a plurality of blind holes are arranged inside the composite AlN-SiC ceramic base layer, and the blind holes are filled with metal W, wherein the blind holes are distributed in an array, the diameter of the blind holes is 0.2 mm, and the spacing between adjacent blind holes is 0.4 mm. The size of the ceramic substrate for the heat sink is 8 mm*8 mm, the thickness of the ceramic substrate for the heat sink is 1.0 mm, the depth of the blind holes is 0.7 mm, and the thickness of the TiAlN coating is 50 nm.

[0050] A method for preparing a ceramic substrate for a heat sink comprises the following steps: S1. 100gAlN-SiC powder, 5g yttrium fluoride, 300ml ethanol were mixed and ball-milled, and then 3g polyvinyl alcohol was added to obtain a slurry. The front blade height of the casting machine was set to 2.0mm, the rear blade height was 1.5mm, and the casting speed was 0.20m / min. The slurry after degassing was poured into the casting machine film belt and dried for 2 hours at a variable temperature to obtain a 0.75mm thick blank. The blank was placed in a graphite hot pressing sintering furnace and sintered under positive pressure in a fluid nitrogen atmosphere. The N2 pressure was set at 20KPa, the sintering temperature was 1650°C, and the holding time was 5 hours to obtain a composite AlN-SiC ceramic substrate; S2. Punching holes on the composite AlN-SiC ceramic substrate using a laser punching process to obtain a composite AlN-SiC ceramic substrate with blind holes, wherein the blind holes are distributed in an array, the diameter of the blind holes is 0.15 mm, the spacing between adjacent blind holes is 0.4 mm, the size of the heat sink ceramic substrate is 8 mm*8 mm, the thickness of the heat sink ceramic substrate is 1.0 mm, and the depth of the blind holes is 0.7 mm. Then, the composite AlN-SiC ceramic substrate with blind holes is immersed in 200 ml of phosphoric acid, immersed for 1 hour and taken out; S3. Injecting molten metal W slurry into the blind hole, sintering at 1500°C and polishing, cyclically sintering - polishing steps 3 times to obtain a composite substrate; S4. The composite substrate is heated to 100°C, and at a pressure of 50Pa, 1g of titanium tetrachloride is adsorbed onto the surface of the composite substrate, and then 2g of trimethylaluminum is added. After fumigation for 60s, excess TMA is flushed away with an inert gas, and then 5ml of ammonia water is dripped into the reaction to form a TiAlN layer with a thickness of 50nm, thereby obtaining a ceramic substrate for a heat sink.

[0051] Comparative Example 1 A ceramic substrate for a heat sink, other contents of which are the same as those of embodiment 1, except that no blind holes are included.

[0052] Comparative Example 2 A ceramic substrate for a heat sink, the other contents of which are the same as those of Example 1, except that titanium (CAS No. 7440-32-6) with a thermal conductivity of 22 W / (m·K) is filled in the blind hole.

[0053] Comparative Example 3 A ceramic substrate for a heat sink, the other contents of which are the same as those of Example 1, except that AlN-SiC is replaced by AlN.

[0054] Comparative Example 4 A ceramic substrate for a heat sink, other contents of which are the same as those of Example 1, except that a TiAlN layer is not included.

[0055] Comparative Example 5 A ceramic substrate for a heat sink, the other contents of which are the same as those of Example 1, except that the TiAlN layer is replaced by a Ti layer.

[0056] Test and Evaluation The mechanical properties, thermal conductivity and bonding ability with the Cu layer of the ceramic substrate for heat sink obtained in the test examples and comparative examples were evaluated, wherein the thermal conductivity was evaluated by testing the thermal resistance according to GB / T 10294-2008, the mechanical properties were evaluated by testing the strength of the ceramic substrate according to GB / T 4740-2024, and the bonding ability with the Cu layer was tested according to GB / T 39685-2020, and the results are shown in Table 1. The lower the thermal resistance, the better the heat dissipation performance.

[0057] Table 1 Performance test results

[0058] It can be seen from the data in Table 1 that compared with Example 1, Comparative Example 1 has no blind holes, its thermal resistance increases significantly, the heat dissipation performance decreases, and the compressive strength does not change much; compared with Example 1, the metal filled in the blind hole of Comparative Example 2 is different, and the thermal conductivity of titanium is less than that of AlN-SiC, the thermal resistance increases, and Comparative Example 2 fails to achieve the improvement of the heat dissipation performance of the ceramic substrate; compared with Example 1, Comparative Example 3 replaces AlN-SiC with AlN, and the thermal conductivity of AlN is higher than that of AlN-SiC, but the overall thermal resistance of the ceramic substrate of Comparative Example 3 increases instead. The reason is that the thermal conductivity of the W metal in the hole is not much different from that of AlN, and a fast heat diffusion channel cannot be formed. At the same time, due to the replacement of AlN-SiC with AlN, the mechanical strength of the material is also greatly reduced; compared with Example 1, Comparative Examples 4 and 5 replace the TiAlN layer, which causes a significant reduction in the bonding force and mechanical strength of the ceramic substrate and the metal layer, while the thermal resistance does not change much.

[0059] From the comparison of Examples 1-3, it can be seen that the density of blind holes affects thermal resistance and compressive strength, and the density of blind holes within the specified range of the present application is more conducive to improving both thermal resistance and compressive strength. From the comparison of Example 1 and Example 4, it can be seen that if the TiAlN layer is too thin, the bonding force and mechanical strength between the ceramic substrate and the metal layer will be greatly reduced.

[0060] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A ceramic substrate for a heat sink, characterized in that: The invention comprises a composite AlN-SiC ceramic base layer and a TiAlN coating layer deposited on the surface of the composite AlN-SiC ceramic base layer. A plurality of blind holes are arranged inside the composite AlN-SiC ceramic base layer, and metal W is filled in the blind holes.

2. The heat sink ceramic substrate according to claim 1, characterized in that: The thermal conductivity of the metal W is greater than the thermal conductivity of the AlN—SiC.

3. The heat sink ceramic substrate according to claim 1, characterized in that: The thickness of the TiAlN coating is 100-300 nm.

4. A method for preparing a ceramic substrate for a heat sink according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Using AlN-SiC, a sintering aid, a binder, and an organic solvent as raw materials, a composite AlN-SiC ceramic substrate is obtained by tape casting; S2. Using a laser drilling process, punching holes on the composite AlN-SiC ceramic substrate to obtain a composite AlN-SiC ceramic substrate having a blind hole; S3. Filling the blind hole with metal W slurry to obtain a composite substrate; S4. In-situ depositing a TiAlN coating on the composite substrate to obtain the ceramic substrate for the heat sink.

5. The method for preparing a ceramic substrate for a heat sink according to claim 4, characterized in that: In step S1, the sintering aid includes one or more of yttrium oxide and yttrium fluoride; the binder includes one or more of polyvinyl alcohol and polyvinyl pyrrolidone; and the organic solvent includes one or more of ethanol, n-butanol, and triethyl phosphate.

6. The method for preparing a ceramic substrate for a heat sink according to claim 4, characterized in that: In step S1, the sintering temperature of the tape casting method is 1600-1700°C.

7. The method for preparing a ceramic substrate for a heat sink according to claim 4, characterized in that: Between step S2 and step S3, the method further includes the step of soaking the composite AlN-SiC ceramic substrate provided with the blind holes in a phosphoric acid solution.

8. The method for preparing a ceramic substrate for a heat sink according to claim 4, characterized in that: In step S3, after filling the metal W slurry, a polishing step is also included.

9. The method for preparing a ceramic substrate for a heat sink according to claim 4, characterized in that: In the step S4, the step of in-situ depositing the TiAlN coating is: using trimethylaluminum, titanium tetrachloride and ammonia as precursors, and utilizing a thermal atomic layer deposition process to prepare the TiAlN coating on the composite substrate.

10. Use of the ceramic substrate for a heat sink according to any one of claims 1 to 3 in a heat sink assembly.

Citation Information

Patent Citations

  • Composite ceramic substrate and its making method

    CN103086745A

  • Film plating method of aluminium nitride ceramic substrate

    CN105506624A

  • Preparation method of SiC-AlN composite ceramic with high thermal conductivity

    CN113121252A

  • Manufacturing method for ceramic substrate with via hole

    JP2004273928A

  • AI Acoustic Image Camera

    KR1020220098659A